Kajian Struktural dan Nilai Moral Dalam Cerita Pendek Keagamaan Serta Pemanfaatannya Sebagai Bahan Ajar - Trisnawati Trisnawati (Universitas Mathla'ul Anwar Banten, 2015)
Purpose of this study are (1) to describe the structure of religious short stories, (2) to describe the values ​​embodied in religious short stories, and (3) to describe the utilization of research results and decrypt religious stories as a literary appreciation of the teaching materials from structural analysis of the values ​​of the short story. The research is conducted as a qualitative descriptive study. Research data collection technique is done by using library or documentation study on religious stories. Steps in collecting data are reading religious short stories carefully, noting the appropriate data, identifing and classifing the data and making the data tabulation. Results of this studies stated that religious stories are built by two elements, facts and means story includes plot, character, and setting, point of view, style and theme and element of the story that are values ​​contained in the story, especially moral values.